2021
DOI: 10.1364/ol.431451
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved dual-comb spectroscopy with a single electro-optic modulator

Abstract: Time-resolved near-infrared absorption spectroscopy of single non-repeatable transient events is performed at high spectral resolution with a dual-comb interferometer using a continuous-wave laser followed by a single electro-optic amplitude modulator. By sharing high-speed electrical/optical components, our spectrometer greatly simplifies the implementation of dual-comb spectroscopy and offers a high mutual coherence time, measured up to 50 s, without any active stabilization system and/or data processing. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The DCS technique allowing fast measurements is especially well suited for monitoring of transient chemical phenomena. [7,8] Proof-of-principle demonstrations and high impact experiments have been carried out in the MIR region with DCS approach, confirming its efficiency in trace gas detection, [6] high resolution molecular spectroscopy, [9] and studies of chemical reaction kinetics. [7] The combination of a high resolution and broad spectral coverage proves very useful in atmospheric [10] and combustion monitoring.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The DCS technique allowing fast measurements is especially well suited for monitoring of transient chemical phenomena. [7,8] Proof-of-principle demonstrations and high impact experiments have been carried out in the MIR region with DCS approach, confirming its efficiency in trace gas detection, [6] high resolution molecular spectroscopy, [9] and studies of chemical reaction kinetics. [7] The combination of a high resolution and broad spectral coverage proves very useful in atmospheric [10] and combustion monitoring.…”
mentioning
confidence: 68%
“…The DCS technique allowing fast measurements is especially well suited for monitoring of transient chemical phenomena. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when compared to on-chip microresonator comb sources based on the Kerr effect, the advantages of our EO approach include less stringent requirement on dispersion, flexibility with comb line spacing, ability to operate at low optical powers, and simultaneous operation at a number of different frequencies. Unlike with non-resonant EOcomb synthesizers 30 , our EO microrings do not allow dual-comb generation in a single generator straightforwardly. Driving the microring at two distinct RF frequencies generates a forest of sidebands, as each sideband within the microring resonances becomes modulated by each radio-frequency signal 31 .…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that mode-locked lasers with a repetition rate of 1 GHz enable data acquisition much faster than that of conventional THz pump–probe spectroscopy. Over the past five years, we have developed ASOPS-based spectroscopic techniques with optical frequency combs and repetition-frequency-stabilized lasers, which have substantially enhanced the dynamic range of time delay scanning and improved the data acquisition speed. Recently, we demonstrated that ASOPS-based two-dimensional electronic spectroscopy (2DES) with two synchronized repetition-frequency-stabilized lasers could break the technical limitations of conventional 2DES regarding the data acquisition rate and the time resolution. , However, there has been no experimental demonstration of asynchronous sampling two-color TA measurements in the mid-IR (MIR) spectral range, except for a few reports on the MIR dual-comb spectroscopy, which is a linear spectroscopic technique. …”
Section: Introductionmentioning
confidence: 99%